Hadith #2605 - Sunan Abi Dawud - Amarh bin Hdyd al-Bjly عمارة بن حديد البجلي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
It was rarely that the Messenger of Allah (ﷺ) set out on a journey on any day but on a Thursday.
Grade: Sahih

Hadith #4729 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر; Waki' bin al-Jarrah وكيع بن الجراح; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
When we are were sitting with the Messenger of Allah (May peace be upon him) he looked at the moon on the night when it was full, that is, fourteenth, and said : You will see your Lord as you see this (moon) and have no doubts about seeing him. If, therefore, you can keep from being prevented from prayer before the sun rises and before it sets, do so. He then recited :”Celebrate the praise of your Lord before the rising of the sun and before its setting”.
Grade: Sahih

Hadith #5018 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
A believer’s vision is the forty-sixth part of Prophecy.
Grade: Sahih

Hadith #5065 - Sunan Abi Dawud - Abu Hurairah; Amr bin 'Asim al-Kalabi عمرو بن عاصم الكلابي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
The Prophet (ﷺ) said: There are two qualities or characteristics which will not be returned by any Muslim without his entering Paradise. While they are easy, those who act upon them are few. One should say: “Glory be to Allah” ten times after every prayer, “Praise be to Allah” ten times and “Allah is Most Great” ten times. That is a hundred and fifty on the tongue, but one thousand and five hundred on the scale. When he goes to bed, he should say: “Allah is Most Great” thirty-f
Grade: Sahih

Hadith #5231 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
Ghalib said: When we were sitting at al-Hasan’s door, a man came along. He said: My father told me on the authority of my grandfather, saying: My father sent me to the Messenger of Allah (ﷺ) and said: Go to him and give him a greeting. So I went to him and said: My father sends you a greeting. He said: Upon you and upon your father be peace.
Grade: Hasan